2003
DOI: 10.1046/j.1439-0434.2003.00744.x
|View full text |Cite
|
Sign up to set email alerts
|

Pathotype Separation of Plasmodiophora brassicae by the Host Plant

Abstract: Different pathotypes existing in the field isolate ‘e’ of Plasmodiophora brassicae were separated by repeated propagation in resistant host plants or by inoculation with single spores. The resulting isolates were studied by combining the molecular markers of fingerprint‐like patterns and characterization of pathogenic capacity using genetically homogenous Arabidopsis ecotypes under controlled environmental conditions, so that the selection of virulent pathotypes within resistant host plants could be demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 23 publications
1
66
0
Order By: Relevance
“…The selection isolate eH (Fähling et al 2003), belonging to pathotype 1, was used in all experiments. The isolate is maintained on roots of the universal susceptible host Chinese cabbage (B. rapa subsp.…”
Section: Plant and Pathogen Materialmentioning
confidence: 99%
“…The selection isolate eH (Fähling et al 2003), belonging to pathotype 1, was used in all experiments. The isolate is maintained on roots of the universal susceptible host Chinese cabbage (B. rapa subsp.…”
Section: Plant and Pathogen Materialmentioning
confidence: 99%
“…Field populations of P. brassicae are heterogenic, and therefore introducing CR cultivars into infested soil has been considered to result in the appearance of highly virulent races through selection from the populations (Seaman et al 1963;Jones et al 1982;Kageyama et al 1995;Fähling et al 2003). In this work, races that were highly virulent to CR cultivars were not detected from the SSGs.…”
Section: Pathogenicity Of Populations Isolated From Ssgsmentioning
confidence: 82%
“…Analysis of the relation between the diversity of pathogenicity (races and pathotypes) and DNA polymorphisms in P. brassicae populations has been tried by some workers (Buhariwalla et al 1995;Möller and Harling 1996;Yano et al 1997;Manzanares-Dauleux et al 2001;Fähling et al 2003). Yano et al (1997) reported that RAPD analysis was able to clearly differentiate Williams' race 9 populations from other race populations (races 1 and 4) but unable to differentiate virulent populations from avirulent ones on CR cultivars of Chinese cabbage bred in Japan.…”
Section: Discussionmentioning
confidence: 99%